2020
DOI: 10.3390/ijerph17041417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Quality of Life in Patients before and after Coronary Artery Bypass Grafting (CABG): A Prospective Study

Abstract: The aim of this study was to examine the quality of life and to report on the utility and QALY measures in patients before and after coronary artery bypass grafting (CABG); to investigate whether the SF-12 is comparable with the SF-36 for measuring health-related quality of life of patients with CABG; and to determine the impact of individual predictors on poor quality of life assessment after rehabilitation. This prospective study was conducted between January 2017 and December 2018 at the University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 45 publications
0
51
1
4
Order By: Relevance
“…Pulmonary rehabilitation, in addition to increasing oxygen consumption and exercise capacity, improves the QoL of patients undergoing cardiac surgery [48]. In this study, the QoL of patients was [51]. In the literature, most of the improvement in both physical and mental component summary of QoL has been reported to occur in the first 6 months in CABG patients [52,53].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Pulmonary rehabilitation, in addition to increasing oxygen consumption and exercise capacity, improves the QoL of patients undergoing cardiac surgery [48]. In this study, the QoL of patients was [51]. In the literature, most of the improvement in both physical and mental component summary of QoL has been reported to occur in the first 6 months in CABG patients [52,53].…”
Section: Discussionmentioning
confidence: 84%
“…Valkenet et al (2017), as a result of the study in which they examined the effect of inspiratory muscle exercises on QoL, reported that there was no improvement in quality of life scores [ 50 ]. Pačarić et al (2020) revealed that one month after CABG, the QoL increased, however, it was still insufficient [ 51 ]. In the literature, most of the improvement in both physical and mental component summary of QoL has been reported to occur in the first 6 months in CABG patients [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of the study population were familiar about dental problems associated with cardiac pacemakers, 24.6% about CABG (Coronary Artery Bypass Graft) and 41.6% were aware of dental problems associated with heart valve replacement (Stent) procedure. Kamath et al [6], Pacaric et al [8], Cruz-Pamplona et al [9] and Cotti et al [10] suggested modified dental treatment and procedural considerations in cardiac disease patients with recent cardio-thoracic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Comparação de escores de predição de mortalidade em pacientes submetidos a cirurgia cardíaca INTRODUÇÃO A cirurgia cardíaca proporciona aumento na expectativa de vida e melhora do estado geral de saúde em casos em que é recomendada 1 . Dentre as cirurgias cardíacas, a mais realizada é a revascularização do miocárdio (CRM), seguida da cirurgia de troca de válvula (TV) 2 .…”
unclassified